Strategi KHaF dalam Penguatan Bacaan Tulis Al-Qur’an dan Hafalan Surah Santri di Rumah Quran Hasanah, Kota Makassar - Magfirah Ilyas, Nita; Abbas, Gusma Harfiana; Luthfi M, Mochtar; Mundzir, Chaerul (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Rumah Quran Hasanah is a Qur’anic learning institution that regularly implements programs to strengthen Qur’an reading and writing skills as well as surah memorization among its students. This community service activity was initiated in response to the need for a structured and sustainable Qur’anic learning culture, particularly in improving reading fluency, tajwid accuracy, and memorization abilities. The program aimed to describe the implementation of the KHaF strategy in the student development process at Rumah Quran Hasanah. The program was carried out through three main stages: monitoring student progress using memorization control cards, conducting regular halaqah-based learning sessions, and focusing learning materials according to a structured schedule. Activities were held every Monday, Wednesday, and Friday. Monday and Wednesday sessions focused on strengthening Qur’an reading and writing skills, while Friday sessions emphasized surah memorization and prayer recitations. The program involved 22 students who were divided into three groups based on their respective competency levels. The results showed improvements in the Qur’an reading abilities of most participants, particularly in reading fluency and accuracy. In addition, students demonstrated better memorization achievements through consistent and well-monitored guidance. Over the past two years, several students have completed the recitation of the Qur’an more than once and were able to complete surah memorization within approximately six months. The KHaF strategy contributed positively to developing discipline, learning consistency, and a more structured culture of Qur’anic education within the community.